Bioadsorption of lead(II) over the pulp of Acrocomia aculeata - Novak, Alexandra; Yubero, Fátima; Diez-Pérez-Núñez, Diana; Fertonani, Fernando Luis; Britez, Brenda Gisselle Da Silva; Gonzalez, Yenny (Eclética Química, 2021)
The adsorption of lead in aqueous solution onto Acrocomia aculeata pulp was examined. The pulp was characterized in the presence and absence of lead using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG-DTA), and scanning electron microscopy (SEM). Sulfur and oxygen bonds were responsible for adsorbing lead onto the pulp surface. The TG-DTA profile proved that adding sodium azide increases the pulp’s thermal stability until 200 °C. Adsorption data in batch and column systems were analyzed to understand the pulp adsorption compared to other biomaterials. In the batch experiments, the removal efficiency reached a maximum of 91.9% when a solution of 50 ppm of lead was placed in contact with the pulp for 30 min and fit Freundlich isotherm behavior. In the column experiments, the theoretical maximum adsorption capacity was found to be 11.97 mg g–1; more column data is needed to compare column results to other studies. Further studies to improve the pulp adsorption capacity are needed for it to be a competitive biomaterial for water treatment.